SHORT-TERM RESULTS OF SURGICAL INTERVENTION AFTER NEOADJUVANT MULTIDRUG CHEMOTHERAPY WITH SELECTIVE CHEMOEMBOLIZATION OF UTERINE ARTERIES IN PATIENTS WITH INITIALLY UNRESECTABLE CERVIX UTERI CANCER - I. A. Kosenko; E. A. Zhavrid; O. P. Matylevich; T. M. Litvinova; V. S. Dudarev (Опухоли женской репродуктивной системы, 2014)
Due to the poor outcomes of treatment for locally advanced cervix uteri cancer (CUC), new multimodality treatment modes have been recently sought for this patient population, by using neoadjuvant multidrug chemotherapy (MDCT) prior to surgical intervention. Many investigators are inclined to consider this approach to be an alternative to the standard treatment, although a number of issues, among them optimal combination of chemical drugs, are not settled yet.This study has evaluated the short-term results of MDCT with selective chemoembolization of uterine arteries with gemcitabine in 22 CUC patients treated at the N.N. Alexandrov Republican Research-and-Practical Center of Oncology and Medical Radiology in 2007-2009. MDCT courses have been noted to be satisfactorily tolerated, without causing severe adverse reactions. Neoadjuvant treat- ments have provided tumor resectability in 90.9% of the patients, the radicability index being 85%.